Uji Sifat Fisik Cat Tembok yang Memanfaatkan pigmen warna Alami dari Daun Jati - Effendy, Suhardi -; Yulianto, Agus; Yulianti, Ian (Faculty of Mathematics and Natural Science, Universitas PGRI Palembang, 2019)
The purpose of this study was to determine the physical properties of wall paint by utilizing teak leaf extract containing carotenoids as natural dyes. Exploration of teak leaf extract is done by boiling teak leaves using 350 ml of water until boiling and filtering with screen mash T100. As an adhesive used 75 grams of tapioca flour and quicklime mixture with a composition ratio of 1: 3, 1: 1 and 3: 1. The solvents used are aqudes and fillers are white cement and PVAc glue. In this study the process of making paint is done by mixing all ingredients from pigments, adhesives, and solvents until homogeneous. Testing of the physical properties of paint, carried out through the test density, viscosity, and adhesion. The results of this study indicate that the composition of the most optimum paint formulation is found in the variation of adhesive with a ratio of 3: 1 which results in a density value of 1.26 gr / ml, viscosity 0.26 poise and adhesion power of 95%.